Studi Komparatif Eskatologi Lukas terhadap Pandangan Eskatologi Matius dan Markus - Seri Damarwanti (SANCTUM DOMINE: JURNAL TEOLOGI, 2017)
The eschatology of the Synoptic Gospels gives the same emphasis in the time of fulfilling the prophecies of the Old Testament through the presence of Jesus Christ. Eschatology according to the authors of the Synoptic Gospels refers to the same thing: the Kingdom of God is emphasized and presented in the present and future aspects. It has been present in the midst of humanity by the presence of Jesus Christ into the world at that time and is now present and manifests itself in the presence and work of the Holy Spirit in the life of the believer. At least, the disciples should have done in the future waiting for now. What kind of faith and attitude are required to share in the Kingdom of Heaven. What is different in the three Gospels lies in the principal issue of every evangelist, namely: to Luke, eschatology emphasizes the issue of "immediate" in which the coming of the Son of man to accomplish God's mission for the world will come "soon", in the sense that the accompanying signs already available ; to Matthew, the emphasis is on the "delay" aspect of the waiting period so that Jesus wants the disciples to focus more on what they need to do in this waiting period so that they do not lose that promised part; in Mark, the presence of the Kingdom of God becomes the main point, in which the life of the Kingdom itself is present in the midst of the believers, and on the other hand also awaits the coming of the fulfillment of the coming of the Kingdom of God in the future.